Homeless F.C. - Leong, James; Lee, Lynn (Hong Kong, 2007)
Twice a week in Hong Kong, an unlikely group of men gather to play football. They call themselves the Dawn Team, for all of the players have lived through dark times. Beyond a love for the beautiful game, the one thing that unites these people is the fact that they all know what it is like to be homeless. The Dawn Team is training to take part in the Homeless World Cup in Cape Town. Only eight players can go, and secretly, everyone wants to be chosen. The journey to South Africa is a chance to see the world outside Hong Kong, to meet other homeless people, and to re-assess their own lives. Homeless FC follows the Dawn Team through one tumultuous year. It is a year in which a glimmer of hope touches the men’s lives, fights erupt, new relationships take root, and a few dreams appear to come true. Shocking, intimate and immediate, this film enters the world of people who have fallen through the cracks.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films